Pengaruh Pemberian Nutrisi AB Mix Pada Pembibitan Timun Apel (Cucumis sp.) Secara Hidroponik Sistem Rakit Apung - Winda, Winda; Syah, Bastaman; Bayfurqon, Fawzy Muhammad (JURNAL AGROPLASMA, 2024)
The factor that causes low production of apple cucumbers is the use of seeds and seedlings that are not of good quality. This study aims to determine the effect of AB Mix nutrition on apple cucumber (Cucumis sp.) seedlings hydroponically with a floating raft system. The experiment was carried out at the screen house on Jln. Gang Sejarah, Dusun Kalijaya 1 Rt003/Rw009 North Rengasdengklok Village, Rengasdengklok District, Karawang Regency starting in February 2024. This research method was used using an experimental method using a single-factor Group Random Design (RAK) with 5 treatments that were repeated 5 (five) times, namely: A (0PPM) as control, B (320 PPM), C (640 PPM), D (960 PPM) and (1280 PPM). The effect of the treatment was analyzed using the F test at the 5% level, so to find out the best treatment was to continue with the LSD follow-up test (DMRT) at the 5% level. The results of the study showed that the provision of 640 PPM nutrition had a real effect on the growth synchronicity, plant height, stem diameter, number of leaves, fresh weight, growth success and leaf area. Keywords : apple cucumbers, nurseries, hydroponics